Entre zoophobie et zoolâtrie : l’animal dans les cultures alimentaires et religieuses - Christophe Lemardelé (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
In his book on the pig taboo in the ancient Near East, Max D. Price demonstrates that the taboo evolved over a long period of time: an alien element of a food culture became a religious prohibition. Whether or not an animal is eaten or sacrificed leads us to consider that each society has a particular relationship with one or several animal species, and this relationship differs greatly depending on whether the society is hunter-gatherer or agricultural. In today’s world, where pets have become very important, this relationship is still evolving and will give rise to new food cultures.